Bibliometric science indicators applied to environmental impacts research (2018)
The growth and development of research on environmental impacts in terms of publications such as the Web of Science sample are analyzed during the period 2007-2018 using HistCite to learn about a global ranking, citations, article impact, keywords and research trends in this area. The research trend increased during the years 2014 and 2017. The United States is the country with the highest number of publications. The Journal of Cleaner Production is the journal with the highest number of publications, along with Science of Total Environment and the Environmental impact assemble review.